Colombia : Arrangement Under the Flexible Credit Line; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Colombia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses an arrangement under the Flexible Credit Line (FCL) for Colombia. Colombia is well placed to confront challenges posed by the ongoing global downturn. Access under an FCL arrangement of SDR 6.966 billion, which the authorities intend to treat as precautionary, would support Colombia's policy framework and strategy, while reducing the likelihood of balance of payments pressures stemming from a change in investor sentiment. IMF staff believes that Colombia fully meets the FCL qualification criteria, and recommends approval of the arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet